Long hospitality careers – a contradiction in terms?. Issue 11 (14th November 2016) - Mooney, Shelagh K.; Harris, Candice; Ryan, Irene
Abstract : Purpose: The purpose of this paper is to explore why workers remain in long hospitality careers and to challenge the frequent portrayal of careers in the sector as temporary and unsatisfactory. Design/methodology/approach: The study took an interpretative social constructionist approach. Methods used were memory-work, semi-structured interviews and intersectional analysis. Findings: A key finding in this study is that career longevity in hospitality is not solely dependent on career progression. Strong social connection, a professional self-identity and complex interesting work contribute to long careers. Research limitations/implications: The study contributes detailed empirical knowledge about hospitality career paths in New Zealand. Conclusions should be generalised outside the specific context with caution. Practical implications: The findings that hospitality jobs can be complex and satisfying at all hierarchical ranks hold practical implications for Human Resource Managers in the service sector. To increase career longevity, hospitality employers should improve induction and socialisation processes and recognise their employees' professional identity. Social implications: This paper significantly extends the notion of belonging and social connection in service work. "Social connection" is distinctly different from social and networking career competencies. Strong social connection is created by a fusion of complex social relationships with managers, co-workers and guests, ultimately creating the sense of a respected professional identity and satisfying career. Originality/value: The contemporary concept of a successful hospitality career is associated with an upwards career trajectory; however, this paper suggests that at the lower hierarchical levels of service work, many individuals enjoy complex satisfying careers with no desire for further advancement.